Global monitoring with the BIS international banking statistics - McGuire, Patrick M.,Tarashev, Nikola A. (Bank for Internat. Settlements, 2008)
This paper illustrates various applications of the BIS international banking statistics. We first compare international bank flows to measures of real activity and liquidity and show that the international banking system is becoming a more important conduit for the transfer of capital across countries. We then use network analysis tools to construct a bird's eye view of the structure of the international banking market and to identify key financial hubs. Linking this information with balance of payments statistics helps to better understand the role of banks in the financing of current account flows, for example the recycling of petrodollars and Asian surpluses. Finally, the paper illustrates how the BIS statistics can be used to analyse internationally active banks' foreign exposures to credit risk and, thus, spot vulnerabilities in the international banking market
Keywords: Arbeitspapier; Graue Literatur; 653; s; International banking; foreign exposures; offshore centres; stress testing; petrodollars; Asian surplus; Finanzsystem; Bankenliquidität; Kapitalmobilität; Bankenstatistik; Welt; Netzwerkanalyse